PENGELOLAAN DIKLAT (Pendidikan dan Pelatihan) PADA BLKK ABD ROZZAAQ DI KOTA BOGOR - Dizki Alfaizal Muktar, Muhammad; Alendra Yusiyaka, Rahmi (LPPM Universitas Ibn Khaldun, Bogor, 2025)
study aims to describe the management of barista training and its impact on improving participants’ competencies at the Abd Rozzaaq Community Training Center in Bogor City. The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research subjects included institutional managers, training instructors, and barista training participants. The findings indicate that the training management was implemented through the stages of planning, implementation, and evaluation, which were arranged systematically and adapted to the participants’ needs and conditions. The planning stage involved the preparation of the curriculum, training materials, and activity schedules, while the implementation emphasized a balance between theory and practice. Evaluation was conducted to assess both the training process and outcomes. The barista training had a positive impact on improving participants’ competencies, including increased knowledge of coffee and brewing techniques, practical skills such as preparing coffee-based beverages, and work attitudes reflecting discipline, responsibility, and service ethics. Thus, the applied training management is proven to contribute to participants’ readiness to enter the workforce, particularly in the coffee industry.